PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI IPA SMAN 12 PADANG - Ulum, Ahmad Mazra’atul; Tasman, Fridgo (Departemen Matematika, 2024)
Mathematics Learning Outcomes can serve as a measure of the effectiveness of a learning process. Nevertheless, the academic achievements in mathematics among the twelfth-grade science students at SMAN 12 Padang remain subpar. Passive classroom learning styles, which minimise student participation, are the main cause of this problem. A better learning approach is needed to improve student achievement. This research implemented the TSTS cooperative learning model. This research investigates whether the implementation of TSTS can improve the learning outcomes of students in class XII SMAN 1 Padang compared to traditional learning methods. In this research, a quasi-experimental non-equivalent control group design was implemented. The researchers found that the mathematics learning outcomes of students of class XII MIPA SMAN 12 Padang were better through TSTS model compared to direct learning model.Keywords– learning outcomes, Two Stay Two Stray